2015
DOI: 10.1177/1747493015607519
|View full text |Cite
|
Sign up to set email alerts
|

Trends in risk of recurrence after the first ischemic stroke in adults younger than 55 years of age in Sweden

Abstract: Background: Previous studies on stroke recurrence in younger adults often contain small sample size which makes it difficult to study trends in stroke recurrence over a long period of time.Aims: The aim of the present study was to investigate temporal trends in the risk of recurrence in younger patients with a first ischemic stroke.Methods: All men and women aged 18-54 years who had survived at least 28 days after a first ischemic stroke from 1987 to 2006 were identified in the Swedish Inpatient Register. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
(44 reference statements)
0
12
3
1
Order By: Relevance
“…Findings from a nationwide register of stroke patients suggest that the reduction in the risk of stroke recurrence observed over time was mainly due to the decrease in the early risk of stroke recurrence. In contrast, temporal trends of the long‐term risk of recurrence showed no significant variation over time 21. However, this study was subjected to selection bias in that only young patients were included.…”
Section: Discussionmentioning
confidence: 95%
“…Findings from a nationwide register of stroke patients suggest that the reduction in the risk of stroke recurrence observed over time was mainly due to the decrease in the early risk of stroke recurrence. In contrast, temporal trends of the long‐term risk of recurrence showed no significant variation over time 21. However, this study was subjected to selection bias in that only young patients were included.…”
Section: Discussionmentioning
confidence: 95%
“…A few previous studies also demonstrated trends in the incidence of recurrent stroke. The 4-year cumulative risk of recurrent IS in Sweden was 11.8% in men and 9.8% in women during a 5-year period (2002–2006) [10]; the values from previous studies were slightly lower [9,17,18]. According to another Swedish study, the risk of recurrent IS decreased by 55%over time in younger stroke patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations on recurrent strokes in young adults usually involve small sample sizes, making it difficult to study the long-term trend of stroke recurrence (Giang et al, 2016). Therefore, we performed a meta-analysis to clarify the inconsistencies between previous studies, and to establish a comprehensive picture of gene-disease associations.…”
Section: Discussionmentioning
confidence: 99%